The fight for the legal framework of the solidarity economy in Brazil: Republican deficit and movimentalist ethos (Cultura Económica, 2019)
In the last two decades, the establishment of an adequate legal framework for the solidarity economy has been one of the central points on its agenda in Brazil. Some progress was made, but obstacles and uncertainties persist to this day, despite the political activism of the social actors involved. In addition to the fact that the solidarity economy faces great opposition from traditional sectors, some crucial barriers - such as the democratic weakness of the country - demand a continuous effort of "institutional work" to change the current framework, in favour of non-capitalist forms of economy. To address these issues, after exposing the process of emergence of the solidarity economy in Brazil, and the political convergences among its actors in legal matters, the article examines the innovations of the current proposals of a national law, highlighting the main obstacles to its approval and establishment. As an example of these difficulties, the article analyses the new law on worker cooperatives, a crucial element for both the solidarity economy and the cooperative sector in Brazil.
Keywords: SOLIDARITY ECONOMY; BRAZIL; LEGAL FRAMEWORK; DEMOCRACY; WORK COOPERATIVES